The Imperfect Match of Public Accountability of State-Owned Enterprises and Private-Sector-Type Financial Reporting: The Case of Italy - Francesco Capalbo; Ricardo Palumbo (Australasian Accounting, Business and Finance Journal, 2013)
State-owned enterprises (SOEs) are legally private entities used in many jurisdictions to satisfy public needs, mostly through extensive consumption of public funds. While the nature of purposes pursued and of resources employed affects their accountability in a public sense, their financial reporting requirements are set on the basis of their legal form and this may end up generating a misalignment between accountability and reporting. Such a misalignment significantly impairs the effectiveness of financial reporting and limits the relevant public authorities’ ability to control. The case of Italian SOEs is a fine example. These were created as incorporated entities fully or partially owned by local governments willing to dislocate the production of public services, especially utilities. Such companies have benefitted, thanks to the chosen legal form, from a private style financial reporting model that has significantly eased the controls normally existing on public administrations, and which has favoured massive misuse of public funds and largely illegal management conducts. This paper advocates for significant amendments to the financial reporting model they inherit from the legal form, in order to realign their private-style accounting obligations with their public-style accountability.
Keywords: State owned enterprises; Accountability; Reporting; Statement of Corporate Intent.